New large-volume detector at the Baksan Neutrino Observatory: Detector prototype. Issue 1 (February 2021) - Ushakov, N A; Fazliakhmetov, A N; Gangapshev, A M; Gavrin, V N; Ibragimova, T V; Kochkarov, M M; Kazalov, V V; Kudrin, D Yu; Kuzminov, V V; Lubsandorzhiev, B K; Lukanov, A D; Malyshkin, Yu M; et al.
Abstract: At the Baksan Neutrino Observatory (Institute for Nuclear Research of the Russian Academy of Sciences, Moscow) deployed in the Caucasus mountains, it is proposed to create, at a depth corresponding to about 4700 mwe (meter water equivalent), a large-volume neutrino detector on the basis of a liquid scintillator with a target mass of 10 kt. This article describes the current state of the first stage of the project, namely a prototype detector with a scintillator mass of 0.5 t. The design of the detector, the equipment and methods used are described.